EVENT STUDY: ANALISIS REAKSI INVESTOR PADA PUBLIKASI LAPORAN KEUANGAN TAHUNAN - vahini, Yuni Prema; Putra, Nyoman Wijana Asmara (E-Jurnal Akuntansi; Vol 13 No 2 (2015), 2015)
Financial statements are the media that shows a company's financial condition and used as a source of consideration to make investment decisions. This research uses event study to testing the information content of financial statements in the event window for 11 days. The research sample is a group companies that included in the index stocks LQ-45 for five consecutive years from 2009 to 2013, there some 22 companies with 110 observations obtained in the Indonesia Stock Exchange. Hypothesis testing using a paired samples t-test. The results of this test showed no difference reaction of investors in the form of differences in average abnormal return and trading volume stocks before and after publication of financial statements statistically.
Keywords: Event Study, Investors Reaction